Optimization of approximate integration of monotone functions of two variables - Babenko, V. F.; Borodachov, S.V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We solve the problem of optimization of approximate integration of functions of two variables defined on a rectangle and monotonic in each variable by using the quadrature formulas with nodes at points of a rectangle net.